Cartesian moral philosophy and control over human beings - Solano Villarreal, Diana (2016)
This paper presents a deeper analysis of the Cartesian moral philosophy in the Discours de la méthode, Les passions de l’âme, and the Principia Philosophiae, also in search of arguments to make clear a relation of connection control of some human beings on other, and the mechanism by which this control hypothetical relationship between humans could manifest.